High-Sensitivity Biosensor-Based Enhanced SPR by ZnO/MoS2 Nanowires Array Layer with Graphene Oxide Nanosheet - Shiliang Guo; Xiaogang Wu; Zhiquan Li; Kai Tong (International Journal of Optics)
A novel SPR biosensor that can achieve a high sensitivity is proposed; therefore, a new prism coupling structure based on metal nanowires array layer is designed in this paper. The thickness of each medium layer for the structure is analyzed to obtain the optimal SPR spectrum, by the finite element method, so that the sensitivity is able to be enhanced greatly. The optimal thicknesses of each medium layer are given, and the sensitivity of the SPR biosensor can reach as high as 210.75°/RIU for the refractive index of the sensing medium, from 1.30 to 1.38.